Roots of Lithospermum erythrorhizon promotes retinal cell survival in optic nerve crush-induced retinal degeneration. (February 2021) - Kang, Tae Kyeom; Le, Tam Thi; Kim, Kyung-A; Kim, Young-Joo; Lee, Wook-Bin; Jung, Sang Hoon
Abstract: Lithospermum erythrorhizon ( L. erythrorhizon ), used in traditional medicine, is a potent wound healing, anti-inflammatory and antioxidant plant. However, the effects of L. erythrorhizon on retinal degenerative diseases remain unknown. Here, we explored the protective effects of L. erythrorhizon in in vitro and in vivo retinal degeneration. We found that ethanol extract of L. erythrorhizon (EELE) and the dichloromethane fraction of L. erythrorhizon (MCLE) significantly increased cell viability under glutamate/BSO-induced excitotoxicity/oxidative stress in R28 cells. Treatment with EELE and MCLE reduced the intracellular reactive oxygen species (ROS) and the levels of apoptotic proteins, such as cleaved PARP and cleaved caspase-3. Furthermore, oral administration of EELE and MCLE in an in vivo optic nerve crush mouse model decreased RGC cell death and increased retinal thickness. The major compound between EELE and MCLE was found to be lithospermic acid A (LAA), which has been shown to prevent the elevation of ROS in R28. Therefore, EELE and MCLE have protective effects against the death of retinal cells in vitro and in vivo, and the major compound, LAA, has an antioxidant effect on retinal cells, suggesting that EELE and MCLE could be beneficial agents for retinal degenerative diseases, including glaucoma. Graphical abstract: Image 1 Highlights: EELE and MCLE significantly increased cell viability against excitotoxicity/oxidative stress-induced cell death. EELE and MCLE reduce the production of ROS and the levels of apoptotic proteins. EELE and MCLE decreased RGC cell death and increased retinal thickness in an optic nerve crush mouse model. Lithospermic acid A, commonly found in EELE and MCLE, decreases ROS production in retinal cells.